Clinical experience with lung-specific electromagnetic transponders for real-time tumor tracking in lung stereotactic body radiotherapy. (October 2019) - Jaccard, Maud; Champion, Ambroise; Dubouloz, Angèle; Picardi, Cristina; Plojoux, Jérôme; Soccal, Paola; Miralbell, Raymond; Dipasquale, Giovanna; Caparrotti, Francesca
Highlights: 7 patients were implanted with lung-specific electromagnetic transponders (EMT). We report no complications from implantation and no migration of the EMT. 7 non-small cell lung cancer patients underwent SBRT using EMT real-time tracking. SBRT was delivered in free-breathing (FB) or in deep inspiration breath-hold (DIBH). Abstract: Background and purposes: Motion management is crucial for optimal stereotactic body radiotherapy (SBRT) of moving targets. We aimed to describe our clinical experience with real-time tracking of lung-specific electromagnetic transponders (EMTs) for SBRT of early stage non-small cell lung cancer in free-breathing (FB) or deep inspiration breath-hold (DIBH). Material and methods: Seven patients were implanted with EMTs. Simulation for SBRT was performed in FB and in DIBH. We prescribed 60 Gy in 3, 5 or 8 fractions to the tumor and delivered SBRT with volumetric modulated arcs and a 6 MV flattening filter free photon beam. Patients' setup at the linac was performed using EMT positions and cone-beam CT (CBCT) verification. Four patients were treated in DIBH because of a dosimetric benefit. We analysed patient alignment and treatment delivery parameters using DIBH or FB and EMT real-time tracking. Results: There were no complications from the EMT implantation. Visual inspection of CBCT before and/or after SBRT revealed good alignment of structures and EMTs. The median setup time was 9.8 min (range: 4.6–34.1 min) and the median session time was 14.7 min (range: 7.3–36.5 min). EMT positions in lungs remained stable during overall treatment and allowed real-time tracking both in FB and in DIBH SBRT. The treatment beam was gated when EMT centroid position exceeded tolerance thresholds ensuring correct delivery of radiation to the tumor. Conclusion: Using EMTs for real-time tracking of tumor motion during lung SBRT proved to be safe, accurate and easy to integrate clinically for treatments in FB or DIBH.